الخطُّ العربيُّ بينَ الأساطيرِ الغَيْبيَّةِ والجُهُودِ البشريَّة: Arabic Calligraphy between Metaphysical Myths and Human Efforts - مصطفى محمد رزق السواحلي (AR-RĀ’IQ, 2023)
لا يُنكرُ مُنصفٌ أنَّ الخطَّ العربيّ الذي اصطفاه الله لتُرْسم به كلماتُ كتابه العزيز قد تيسَّر له من مجالي البهاء والجمال ما لم يتيسَّرْ لغيره، فهو بأشكاله الهندسيَّة البديعة يرسم صورًا جميلةً بلا حدود، حتى صار فنًّا مستقلًّا بذاته، فاكتفى به العربُ عن الصور الفاضحة والتماثيل العارية، وبات هذا التشكيل الهندسيٌّ ملمحًا جماليًّا أعطى الحضارة الإسلاميَّة طابعًا خاصًّا على مرِّ العصور. وقد حمل ذلك الجمالُ الفائقُ نفرًا من العلماء على القول بأنَّه قد نزل من السماء على هذه الصورة البديعة التي هي فوق طاقة البشر، وشحنت كتب التراث العربيّ بعشرات المرويَّات في هذا المجال، وهو ما يحاول هذا البحث تحقيقها، للتفريق بين ما هو غيبيّ يحتاج إلى نصٍّ قطعيِّ الثُّبوت والدَّلالة، وما هو بشريّ من نتاج الجهود المتراكمة لخبرات العلماء والمبدعين على مرِّ العصور. وهو ما يقتضي بيان الموقف الوسطيّ الرَّشيد من قضية الغيب عمومًا، ثم عرض عدد من تلك الرِّوايات المتناثرة في بطون كتب التراث العربيّ، ونقدها روايةً ودرايةً، ثم بيان الذين قاموا باستعارة الخطِّ العربيّ من الأمم المجاورة قُبَيْل الإسلام، والذين قاموا بتطويره بعد الإسلام، حتى صار صناعةً إسلاميَّةً بامتياز. وذلك من خلال المنهج الوصفيّ التحليلي، وقد انتهى البحث إلى جملةٍ من النتائج أهمها: أنَّ الإيمان بالغيب واجبٌ إيمانيٌّ بشرط وجود دليلٍ صحيحٍ من الوحي الصحيحِ الثُّبوت والدَّلالة. وتشير معظم الرِّوايات الواقعيَّة إلى أنَّ العرب استعاروا الخطَّ من الأمم المجاورة، وبخاصَّة من الخطِّ النَّبطيِّ في منطقة الأنبار. وأنَّ العروة بين الكتابة والحضارة عروة وثقى لا انفصامَ لها، وهو ما تحقق للعرب بعد ظهور الإسلام مما يجعلنا نقول: إنَّه صناعة إسلاميَّة بامتياز، وإنَّ تتابع جهود العلماء العرب في مجال تطوير الخط العربيّ يؤكِّد أنَّ الخطَّ صناعة بشرية، تطوَّرتْ على أيدي رجال أفنَوْا أعمارَهم في خدمةِ اللغةِ العربيّة علومًا وفنونًا. Abstract in English It is an undoubtedly acknowledgement that Allah has chosen Arabic calligraphy to write the words of the Holy Qur’an, and gave it magnificence and beauty which any other calligraphy does not have. Its exquisite geometric shapes paint unlimited beautiful images, and even became an independent art. The Arabs were contented with it for obscene images and nude statues, and this geometric formation became an aesthetic feature that gave Islamic civilization a special character throughout the ages. This transcendent beauty led a group of scholars in stating that it descended from the divine in this wonderful image, which is beyond the human capacity, and Arabic heritage books were loaded with dozens of narrations in this field. This is what this research attempts to achieve, in order to differentiate between what is the metaphysical that needs a definitive text of proof and significance, and what is human as a product of the cumulative efforts of the experiences of scientists and creators throughout the ages, which requires a rational, moderate position on the issue of the unseen generally, then to present a number of those narrations scattered in the wombs of the books of Arab heritage, and criticize them as a narration and knowledge. Also, to mention those who borrowed Arabic calligraphy from the neighboring nations before Islam, and who developed it after Islam, until it became an Islamic industry par excellence, through the descriptive analytical method. In the end, the research concluded a number of results, the most important of them are: Belief in the unseen is a religious duty, provided that there is a valid evidence from the authentic revelation. Most realistic narrations indicate that the Arabs borrowed their calligraphy from the neighboring nations, especially from the Nabataean script in the Anbar region. The bond between the writing and civilization is an inseparable bond, which was achieved by the Arabs after the advent of Islam, which makes us say: It is an Islamic industry par excellence, and the follow-ups of the efforts of Arab scholars in the field of developing Arabic calligraphy confirm that the calligraphy is a human industry, developed by the scholars who spent their ages serving the sciences and arts in Arabic language.